2018
DOI: 10.14412/2074-2711-2018-1s-38-45
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuroinflammation in the pathogenesis of epilepsy

Abstract: 1192019, Санкт-Петербург, ул. Бехтерева, 3; 2 191015, Санкт-Петербург, ул. Кирочная, 41 За

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…A number of studies have shown a correlation between the severity of epileptic seizures and increased levels of cytokines in the blood plasma ( HMGB-1 , TLR4 , IL-1β , IL-1R1 , and TNF-α ) of patients with drug-resistant epilepsy [ 17 , 27 ]; increased levels of cytokines have also been observed in cerebrospinal fluid ( IL-1β ) [ 16 , 28 ]. The impairment of the profile of pro-inflammatory cytokines in plasma ( IL-1β , IL-6 , IL-8 , TNF-α ) also correlates with the frequency of seizures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown a correlation between the severity of epileptic seizures and increased levels of cytokines in the blood plasma ( HMGB-1 , TLR4 , IL-1β , IL-1R1 , and TNF-α ) of patients with drug-resistant epilepsy [ 17 , 27 ]; increased levels of cytokines have also been observed in cerebrospinal fluid ( IL-1β ) [ 16 , 28 ]. The impairment of the profile of pro-inflammatory cytokines in plasma ( IL-1β , IL-6 , IL-8 , TNF-α ) also correlates with the frequency of seizures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical data demonstrate that neuroinflammation and neurodegeneration involved in epileptogenesis make a significant contribution to the development of drug resistance and the chronicity of TLE [ 16 , 17 ]. The mechanism of development of neuroinflammation and neurodegeneration in TLE has been studied in experimental models as well as in clinical samples of biological fluids and tissues of patients [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studied blood plasma samples, the content of pro-inflammatory IL-1β and its natural anticonvulsant antagonist IL-1RA did not differ significantly from their content in the group of patients without epilepsy. However, there are data indicating a decrease in IL-1RA/IL-1β after an attack [26]. Such differences may be due to the fact that we took blood during the seizure-free period established in the hospital, while other researchers take blood for analysis immediately after a seizure or after a certain time.…”
Section: Cytokines In the Blood And Neuroinflammationmentioning
confidence: 99%
“…У пациентов с медиобазальной височной эпилепсией и склерозом гиппокампа в сыворотке крови обнаружена гиперэкспрессия ИЛ1β [16]. А повышенный уровень ИЛ1β в цереброспинальной жидкости у больных эпилепсией свидетельствует о нарушении гематоэнцефалического барьера и системном воспалении [17]. Выяв-лен ряд точечных маркеров высокопродуцирующего аллельного варианта гена IL1B, наследуемых чаще сцепленно (3953, -3737, -1469, -999).…”
Section: ч а с т о т а н о с и т е л ь с т в а он п R S 1 1 4 3 6 3 4unclassified